IMPLEMENTASI “PAIKEM” DENGAN “COLLABORATIVE LEARNING” (Satu alternatif memecahkan masalah belajar PPKn) - Djoko Apriono (FKIP Unirow Tuban, 2016)
PAIKEM is active, inspirational/Interactive/Innovative, Critical/Creative, Effective, and Fun Learning. PAIKEM based learning helps students develop the ability to think high stage, critical thinking and creative thinking (critical and creative thinking). Collaborative learning involves a combination of hard work or intellectual effort by students working in groups to get a sense, the solution, meaning or create a product, and the overall exploration centered on the student and not the teacher's explanation is simple or detailed. By using collaborative learning, implementation PAIKEM as expected by teachers and public education will be realized and seen the results during the learning process takes place and when the student has been implementing the learning, it will appear on the behavior of students everyday when they exist in the school environment , families and communities, the students are critical, creative, active, interactive, innovative, and able to cooperate with anyone.